2005
DOI: 10.1080/01902140500324828
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOHISTOCHEMICAL STUDY OF TUMOR NECROSIS FACTOR-α, MATRIX METALLOPROTEINASE-12, AND TISSUE INHIBITOR OF METALLOPROTEINASE-2 ON ALVEOLAR MACROPHAGES OF BALB/c MICE EXPOSED TO SHORT-TERM CIGARETTE SMOKE

Abstract: Alveolar cells were evaluated in BALB/c mice exposed to smoke from 9 cigarettes per day. The mice were sacrificed at 1, 5, and 10 days and examined by lung morphometry and immunohistochemical staining of alveolar macrophages for tumor necrosis factor (TNF)-alpha, matrix metalloproteinase (MMP)-12, and tissue inhibitor of metalloproteinase (TIMP)-2. Cigarette smoke (CS)-exposed mice showed a progressive increase in numbers of alveolar macrophages (AMs) up to 10 days. MMP-12 was increased in AMs compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In the CS10, CS20, CS30 and CS60 groups, the II for TNF-α was significantly higher than in the control group. This finding corroborates those of previous studies, (12,16,17,25) which showed a special participation of TNF-α in emphysema induced by cigarette smoke. The II for IL-6 increased progressively in direct relation to increases in the duration of exposure.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the CS10, CS20, CS30 and CS60 groups, the II for TNF-α was significantly higher than in the control group. This finding corroborates those of previous studies, (12,16,17,25) which showed a special participation of TNF-α in emphysema induced by cigarette smoke. The II for IL-6 increased progressively in direct relation to increases in the duration of exposure.…”
Section: Discussionsupporting
confidence: 83%
“…(7,(16)(17)(18) In brief, animals in each study group were placed in the inhalation chamber (40 cm in length, 30 cm in width and…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental animals, exposure to cigarette smoke consistently upregulates MMP-12 production and release [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]; this phenomenon appears to be much more frequent than upregulation of any other MMP, although we make that statement with caution because MMP-12 has been examined much more frequently than other MMPs.…”
Section: Mmps In Emphysema: Mmp-12mentioning
confidence: 67%